Peningkatan Kompetensi Perawa sesuai Level Perawat Klinis (PK) - Sugeng Riyanto; Rr. Tutik Sri Hariyati; Cori Tri Suryani (Journal of Telenursing (JOTING), 2023)
This study aims to improve the competence of nurses according to the PK level by implementing a reminder system for conducting training. The method used is a program innovation report using the ADDIE approach (Assessment Analysis, Design, Development, Implementation, and Evaluation). The results of the research on the initial assessment showed that 98% of nurses still needed training according to Level PK, 82% of room heads who had Continuing Professional Development (CPD) planning, 94% of room heads who still required training to make Continuing Professional Development (CPD). The results of the study after testing the innovation format showed that 88% of respondents said the Nurse Training Data format according to the PK level was easy to use, 88% said the training data format according to the PK Level was constructive in collecting initial data on nurse training and 100% of respondents said they would be happy to fill it out if This format is carried out in hospitals. Then, an innovation was made to make a prototype mapping format for nurse training and a nurse training reminder system according to the PK level. In conclusion, the format mapping and training reminder system for nurses according to the PK level can be recommended after conducting trials on one of the nursing units. Keywords: Competence, Nurse Training According to PK Level